2017
DOI: 10.1002/ldr.2825
|View full text |Cite
|
Sign up to set email alerts
|

Upslope inflow, hillslope gradient and rainfall intensity impacts on ephemeral gully erosion

Abstract: Ephemeral gullies (EGs) are major contributors to sediment loss and land degradation on cultivated lands. However, the topography and rainfall impacts on EG development processes are still unclear, especially on steep loessial hillslopes such as the Loess Plateau. A series of laboratory rainfall simulation experiments were conducted to investigate the impacts of topographic characteristics (3 typical slope gradients (S): 26.8%, 36.4%, and 46.6%; and 5 upslope drainage areas (A): 16, 32, 64, 96, and 128 m2) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…High-intensity rainfall favours the occurrence of surface runoff and rill cutting (He et al, 2017), but this may also occur from saturation overland flow in events of low intensity but long duration (Kirkbride and Reeves, 1993). Xu et al (2017) found in laboratory experiments on gully erosion in a very large soil box that cumulative gully cutting (expressed in terms of the mass of soil removed) increased with rainfall intensity. In Israel, Hoober et al (2017) identified an intensity threshold for the cutting and modification of ephemeral gullies of 12mm h –1 .…”
Section: The Significance Of Rainfall Intensity In Geomorphologymentioning
confidence: 95%
“…High-intensity rainfall favours the occurrence of surface runoff and rill cutting (He et al, 2017), but this may also occur from saturation overland flow in events of low intensity but long duration (Kirkbride and Reeves, 1993). Xu et al (2017) found in laboratory experiments on gully erosion in a very large soil box that cumulative gully cutting (expressed in terms of the mass of soil removed) increased with rainfall intensity. In Israel, Hoober et al (2017) identified an intensity threshold for the cutting and modification of ephemeral gullies of 12mm h –1 .…”
Section: The Significance Of Rainfall Intensity In Geomorphologymentioning
confidence: 95%
“…The low data requirement, small number of variables, and extrapolation to the same region increase the applicability of regression models on annual erosion at the slope scale, though the process dynamics are not precisely presented. For example, with the use of regression models, it was concluded that the soil loss is an exponential function of rainfall intensity, upslope drainage area, and slope on the basis of laboratory experiments (Xu, Zheng, Wilson, & Wu, ). Based on observations made at microplots in an arid environment, it was reported that soil erosion is linearly related to rainfall intensity, slope, and antecedent moisture (Ziadat & Taimeh, ).…”
Section: Introductionmentioning
confidence: 99%
“…(2017) and Wu et al . (2017) both found that soil loss increased with increased rainfall intensity 79 , 80 .…”
Section: Resultsmentioning
confidence: 94%